2022
DOI: 10.1242/bio.059414
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial peptide expression in the cockroach gut during enterobacterial infection is specific and influenced by type III secretion

Abstract: Omnivorous synanthropic cockroaches, such as the German cockroach (Blattella germanica), are reservoirs and vectors of enteric bacterial pathogens. A lifestyle conducive to frequent encounters with high loads of diverse bacteria may have led to the evolution of unique innate immune systems in these insects. The innate immune response of insects relies largely on generalized mechanisms to sense and eliminate foreign microbes. However, analyses of the genomes of common synanthropic cockroaches previously reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…One of the analyzed insects was B. germanica , in which it was detected that hemocytes were located in the dorsal tergum and almost absent in the ventral sternum [ 49 ]. However, it has recently been reported that the expression of attacin-like_g1 , attacin_like_g2 and blattellicin_g1 genes in B. germanica gut is significantly increased after feeding with live Salmonella enterica serovar Typhimurium [ 50 ]. In this work, the expression of these three genes as well as defensin_g1-g2 was also detected at very low levels in control individuals by qRT-PCR (approximate range 10 −4 to 10 −5 ) [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the analyzed insects was B. germanica , in which it was detected that hemocytes were located in the dorsal tergum and almost absent in the ventral sternum [ 49 ]. However, it has recently been reported that the expression of attacin-like_g1 , attacin_like_g2 and blattellicin_g1 genes in B. germanica gut is significantly increased after feeding with live Salmonella enterica serovar Typhimurium [ 50 ]. In this work, the expression of these three genes as well as defensin_g1-g2 was also detected at very low levels in control individuals by qRT-PCR (approximate range 10 −4 to 10 −5 ) [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it has recently been reported that the expression of attacin-like_g1 , attacin_like_g2 and blattellicin_g1 genes in B. germanica gut is significantly increased after feeding with live Salmonella enterica serovar Typhimurium [ 50 ]. In this work, the expression of these three genes as well as defensin_g1-g2 was also detected at very low levels in control individuals by qRT-PCR (approximate range 10 −4 to 10 −5 ) [ 50 ]. The levels of detection by this method compared to our RNAseq analysis were similar (in both cases relative to the expression of EF1A ), except for attacin-like_g1 , which was not detected at all in our samples ( attacin_like_g2 in the three gut sections: range 2 × 10 −3 to 1 × 10 −4 ; blattellicin_g1 in hindgut: 3 × 10 −4 ; defensin_g1-g2 in midgut: 8 × 10 −5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Amplification conditions were as follows: 95 °C for 5 min, followed by 40 cycles of denaturation at 95 °C for 15 s, annealing at 50 °C for 20 s, and extension at 72 °C for 30 s. Cycle threshold (CT) values were obtained for individual insects as a proxy for the bacterial load and analyzed by ANOVA with Dunnett's post hoc test and adjustment for multiple comparisons. The qPCR assays were performed at the University of South Dakota using the laboratory adapted American Cyanamid Orlando Normal strain of B. germanica from a colony maintained as previously described 30 …”
Section: Methodsmentioning
confidence: 99%
“…Two independent replicates were conducted for each nanoparticle, and in each replicate development curves were compared to the control using a Mantel–Cox log‐rank test. The development assays were performed at the University of South Dakota insectary facility using the laboratory adapted American Cyanamid Orlando Normal strain of B. germanica from a colony maintained as previously described 30 …”
Section: Methodsmentioning
confidence: 99%
“…Groups of donor cockroaches were marked with color tags and orally infected with S. Typhimurium as described in our previous studies (Turner et al, 2022 ; Turner & Pietri, 2022 ). In brief, cockroaches were separated into experimental enclosures and starved of food and water for three days, which is sufficient to promote consistent feeding among individuals without causing mortality.…”
Section: Methodsmentioning
confidence: 99%